The Effect of Education on Making Eco Light Trap Using the Demonstration Method as An Effort to Improve DHF Prevention Skills - Errix Kristian Julianto; Lina Wahyuni (Indonesian Journal of Global Health Research, 2025)
Dengue Hemorrhagic Fever (DHF) is a viral disease transmitted by the Aedes Aegypti mosquito. DHF is transmitted through the bite of the Aedes Aegypti mosquito and contains the dengue virus. This study was to determine the effect of education on making eco light traps using the demonstration method as an effort to improve DHF prevention skills in Wedi Village, Kapas District, Bojonegoro Regency. The method used in this research is quantitative with a pre-experimental approach. The population in this study was 538 adults in Wedi Village. The sample in this study was taken using purposive sampling of 36 respondents. Data were collected through pre- and post-observation of respondents' skills after being given education, demonstrations, question and answer sessions, and independent practice of making eco light traps, then the data were analyzed using the Wilcoxon rank sum test. Based on the results of the respondent observation sheet before (pre-test) the demonstration of making Eco Light Trap, it was found that 1 respondent (2.8%) had good skills, 14 respondents (38.9%) were included in sufficient skills, and 21 respondents (58.3%) had poor skills. And after (post-test) the demonstration of making Eco Light Trap, it was found that 31 respondents (86.1%) had good skills. 5 respondents (13.9%) were included in sufficient skills, and none had poor skills. Based on the Wilcoxon analysis test, the p-value was 0.000, which means the significance value is <0.05. This study shows that eco-light trap education as a Dengue Hemorrhagic Fever (DHF) prevention effort can improve community knowledge, attitudes, and behavior in controlling the Aedes aegypti mosquito vector. The application of eco-light traps has proven effective as a simple, environmentally friendly technology that is easy to apply at the household level to reduce mosquito populations.